Business Architecture Model for a microenterprise in the textile sector - Suarez Torres, Betty Lizby; Sangay Cabanillas, Kenia Cinthia; Gratelli Melendez, Fabrizio Alberto; Marreros Arqueros, Eduardo Rodrigo; Baca Rodriguez, Nathaly Marissa (LACCEI, 2024)
The objective of this research is to propose a business architecture model for the company Anghela Barboza Boutique, being of a non-experimental design and of a descriptive-transversal type, it used as an instrument a questionnaire to collect information from the personnel, which were 6 people. and observation of sales process activities. The initial analysis of the process showed a problem generated by inefficient management in decision making, loss of information, delay in customer service and poor management of sales records; Under this problem, improvement proposals emerged based on the use of the TOGAF Framework, related to the business architecture phase or also called process architecture. The result indicates that the application of the proposed model would reduce operating costs by 14%, sales time by 15% and 100% of internal customers perceive that it would support effective decision making, by having the information stored. and treated using information technology tools. Finally, this article is divided into introduction, state of the art, objectives, material and methods, methodology for architectural design, discussion, results and conclusions.